1990
DOI: 10.1007/bf01292865
|View full text |Cite
|
Sign up to set email alerts
|

Zero-motion correlations in high-energy proton elastic scattering on40Ca with noneikonal nucleon-nucleon amplitude

Abstract: Using a noneikonal expression for the two-body scattering amplitude, consistent with the proton-nucleon scattering data, the cross-section of the 1.04 GeV-proton elastic scattering on 4~ is calculated by the GlauberSitenko theoretical scheme in the framework of the coherent density fluctuation model (CDFM) as well as of the independent-particle model (IPM). It is shown that the use of the noneikonal amplitude in the CDFM calculations improves the agreement with the experimental data especially at larger scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, once we accept that the Glauber formalism is a reliable theoretical tool at intermediate energies, it seems important to focus our attention on its basic ingredients. In this context, it may be mentioned that Antonov et al, 8 and Khan and Singh 9 have shown that a better description of the NN amplitude improves the theoretical situation throughout the range of momentum transfer, as compared to the generally used single Gaussian approximation for the NN amplitude. 10 This clearly indicates the importance of a proper choice of the NN amplitude in any realistic study of the proton-nucleus scattering data.…”
Section: Introductionmentioning
confidence: 99%
“…However, once we accept that the Glauber formalism is a reliable theoretical tool at intermediate energies, it seems important to focus our attention on its basic ingredients. In this context, it may be mentioned that Antonov et al, 8 and Khan and Singh 9 have shown that a better description of the NN amplitude improves the theoretical situation throughout the range of momentum transfer, as compared to the generally used single Gaussian approximation for the NN amplitude. 10 This clearly indicates the importance of a proper choice of the NN amplitude in any realistic study of the proton-nucleus scattering data.…”
Section: Introductionmentioning
confidence: 99%